Mortality prediction by acute kidney injury biomarkers in comparison with serum creatinine. (December 2014) - Hiruma, Takahiro; Asada, Toshifumi; Yamamoto, Miyuki; Inokuchi, Ryota; Matsubara, Takehiro; Ishii, Takeshi; Sumida, Maki; Isshiki, Rei; Mayumi, Kengo; Noiri, Eisei; Nangaku, Masaomi; Yahagi, Naoki; et al.
Abstract Objectives: To investigate the performance of acute kidney injury (AKI) biomarkers for mortality prediction. Materials and methods: Cutoff values of urinary L-type fatty acid-binding protein (L-FABP) and N-acetyl-β-d-glucosaminidase (NAG) for AKI diagnosis in ICU were determined in the derivation cohort. The performance of these AKI biomarkers for mortality prediction was evaluated in the validation cohort with stratification of serum-creatinine based AKI diagnosis. Results: Mortality in the AKI patients diagnosed by serum creatinine was increased remarkably when urinary L-FABP and NAG were positive. Conclusions: These AKI biomarkers can specifically detect high-risk patients among creatinine-base diagnosed AKI.